2002
DOI: 10.1128/jvi.76.19.9868-9876.2002
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD4 + T Cells Are the Earliest Detectable Human Immunodeficiency Virus Type 1 (HIV-1)-Infected Cells in the Female Genital Mucosal Tissue during HIV-1 Transmission in an Organ Culture System

Abstract: The virologic and cellular factors that are involved in transmission of human immunodeficiency virus type 1 (HIV-1) across the female genital tissue are poorly understood. We have recently developed a human cervical tissue-derived organ culture model to study heterosexual transmission of HIV-1 that mimics the in vivo situation. Using this model we investigated the role of phenotypic characteristics of HIV-1 and identified the cell types that are first infected during transmission. Our data indicate that the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
119
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 35 publications
10
119
0
2
Order By: Relevance
“…There has been much debate about the mechanisms of HIV infection and entry via the female genital tract, including the importance of epithelial breaches or microabrasions and the cell types involved [16][17][18]. This has become of increasing importance because of the recent problems in vaccine development against , and therefore there is a need for alternative methods to prevent HIV-1 transmission.…”
Section: Lc Interactions With Important Human Viruses Hiv and Lcmentioning
confidence: 99%
“…There has been much debate about the mechanisms of HIV infection and entry via the female genital tract, including the importance of epithelial breaches or microabrasions and the cell types involved [16][17][18]. This has become of increasing importance because of the recent problems in vaccine development against , and therefore there is a need for alternative methods to prevent HIV-1 transmission.…”
Section: Lc Interactions With Important Human Viruses Hiv and Lcmentioning
confidence: 99%
“…4 Furthermore, studies have shown that accumulation of CD4 + T cells in human cervical tissue was detected within 6 h post-HIV infection. 17 Previous study has also reported an increased production of cytokines such as CXCL1 and CXCL10 in culture supernatant of HIV-exposed Ectocervical epithelia were exposed to HIV or control supernatant in an organ culture for 24 h. The tissues exposed to control supernatant were treated with or without 10 mM EDTA in the final 2-h incubation time. HIV-or control supernatantexposed tissues (with or without EDTA) were further exposed to FITC-labeled dextran (3 kDa) for 1 h at 37°C in a CO 2 incubator.…”
Section: Cytokine Gene Expression In Epithelial Cells Following Hiv Ementioning
confidence: 99%
“…15,16 Studies have reported upregulation of TSLP in human cervical epithelial cell lines post-HIV exposure that strongly activates human myeloid dendritic cell (DC), 14 while others have shown accumulation of CD4 + T cells within 6 h post-HIV infection in human cervical tissue. 17 Therefore, epithelial cells may be the first target for HIV to induce local immune activation, which facilitates the establishment of initial HIV infection in the submucosal region.…”
mentioning
confidence: 99%
“…Partially overlapping information could be obtained by experimental analysis of tissue biopsies taken from newly exposed individuals but, in the context of community-acquired infections, characterization of the inocula may not be possible and anti-retroviral therapy may be instigated at the time of patient presentation. Thus, from the standpoint of both controlling and then adjusting experimental variables, there are numerous opportunities and benefits to be derived from studies relying on human organ cultures now that the systems have been validated (Glushakova et al 1995(Glushakova et al ,1999Collins et al 2000;Greenhead et al 2000;Gupta et al 2002;Zhao et al 2004). We have shown that cell-free HIV (HIV96-480, a low passage primary patient isolate) can establish infections in tonsillar leukocytes when infectivity is applied directly Original magnification ϫ100.…”
Section: Discussionmentioning
confidence: 99%